2020
DOI: 10.1038/s41598-020-78064-0
|View full text |Cite
|
Sign up to set email alerts
|

Advanced superhard composite materials with extremely improved mechanical strength by interfacial segregation of dilute dopants

Abstract: Control of heterointerfaces in advanced composite materials is of scientific and industrial importance, because their interfacial structures and properties often determine overall performance and reliability of the materials. Here distinct improvement of mechanical properties of alumina-matrix tungsten-carbide composites, which is expected for cutting-tool application for aerospace industries, is achieved via interfacial atomic segregation. It is found that only a small amount of Zr addition is unexpectedly ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…195)203) Nishi et al successfully attained much improved bending strengths of more than 2 GPa for Al 2 O 3 WC systems with addition of a small amount of ZrO 2 (less than 5 vol %). 204) They produced the fully sintered CMC specimens by a hot-press technique. From STEM and elemental mapping images of the microstructures, it was found that added ZrO 2 segregate mainly at interfaces between Al 2 O 3 and WC grains, forming the atomic-sized thin segregation layers (Fig.…”
Section: Interfacial Strengthening In Al 2 O 3 -Wc Composites By Addi...mentioning
confidence: 99%
“…195)203) Nishi et al successfully attained much improved bending strengths of more than 2 GPa for Al 2 O 3 WC systems with addition of a small amount of ZrO 2 (less than 5 vol %). 204) They produced the fully sintered CMC specimens by a hot-press technique. From STEM and elemental mapping images of the microstructures, it was found that added ZrO 2 segregate mainly at interfaces between Al 2 O 3 and WC grains, forming the atomic-sized thin segregation layers (Fig.…”
Section: Interfacial Strengthening In Al 2 O 3 -Wc Composites By Addi...mentioning
confidence: 99%
“…In this study, alumina (Al 2 O 3 ) matrix tungsten–carbide (WC) composites are focused on because the composites are expected to be utilized as superhard materials for cutting tool applications in the aerospace industry. According to our previous paper, it is found that Al 2 O 3 –WC composites are not only chemically stable but addition of a small amount of Zr ions can induce excellent bending strengths that are twice larger than those previously reported 4 . This can be attained by Zr segregation at the atomic scale along the interfaces between Al 2 O 3 and WC.…”
Section: Introductionmentioning
confidence: 80%
“…The amount of ZrO 2 was selected to be 5 vol% because it was found that the three-point bending strength of the Al 2 O 3 -WC composites stably exceeds 2 GPa. 4 After weighing the respective powders, preliminary pulverization was performed. In the process of preliminary pulverization, Al 2 O 3 and ZrO 2 powders were ball milled for about 20 h with an ethanol solvent using high-purity alumina balls as grinding media.…”
Section: Experiments Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Such materials are mainly employed under harsh conditions, including at high or low temperatures, various conditions of pressure, radiation, constant friction and/ or corrosion, high stress, and others. 4,5 From the chemical point of view, the hardness and stability of these alloys under the action of different factors are due to the low value and sustainability of the covalent bonds. 3,6 The high density of valence electrons in transition metals (d-elements) specifies high values of the volume elastic modulus but reduces their stability at the same time.…”
mentioning
confidence: 99%